Unveiling the Ocean’s Arsenal: Successful Integration of Marine Metabolites into Disease Management - Singh, Ajit Pal; Saxena, Rahul; Saxena, Suyash; Maurya, Neelesh Kumar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The growing problem of antibiotic resistance calls for a paradigm shift in medication discovery. Fortunately, the enormous oceans, home to an incredible diversity of life, provide a viable solution: marine metabolites. These unusual chemicals have enormous potential for treating a wide range of diseases. This present study investigates the great potential for using these marine-derived gems in disease management techniques. Despite the difficulty of procuring and isolating marine organisms, discovering the most effective metabolites, and traversing lengthy research pipelines, the potential rewards are apparent. To demonstrate the power of these marine resources, the paper examines successful case studies. Each case study delves deeply into a single marine metabolite, including its source organism, the disease it targets, and the precise mechanism by which the metabolite disrupts the disease process. We'll look at the results of clinical trials that examined the efficacy and safety of these marine-derived medications, eventually exposing the real-world influence on patient outcomes after incorporating them into treatment plans. Examining these successful cases provides useful insights into the enormous potential of marine resources for producing novel and effective medications, opening the path for further discovery and innovation in the battle against a wide range of diseases.